PENGARUH HARGA, PROMOSI, DAN CUACA TERHADAP KEPUTUSAN PEMBELIANPRODUK BATU SPLIT DI PT BINTANG MERUYA LESTARIJAYA - Cahyati, Ayu; Hamzah, Muhammad Ichwan (JEBI | Jurnal Ekonomi Bisnis Indonesia, 2023)
The purpose of this study is to find out how much influence Price, Promotion, and Weather to Decision at PT Bintang Meruya Lestari Jakarta. This type of research is survey research with quantitative approach, where research is done by taking some samples from the population and using questionnaire as data gathering tools. The population of this study is 85 consumers. In this study using a 85 respondents. The research method used primary data. Sampling technique using Accidental Sampling and processed by using SPSS 21.0. From the results of the study showed that all independent variables (Price, Promotion, and Weather) simultaneously or together effect to Decision at PT Bintang Meruya Lestarijaya. Judging from the value of correlation coefficient (R) of 0.609 there is a strong relationship between Price variables Promotion, and Weather to Decision. Then from the calculation of Coefficient of Determination (R2), it can be concluded that the independent variables in this study has an Adjusted R Square value of 0.347 or 34.7%, it shows that the percentage of contribution variable Price, Promotion, and Weather Giving influence of 34.7%, to Decision at PT Bintang Meruya Lestari Jakarta while the rest equal to 65.3% influenced other factor not included in this research.